2018
DOI: 10.1177/1533033818809993
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-494-3p Promotes Cell Growth, Migration, and Invasion of Nasopharyngeal Carcinoma by Targeting Sox7

Abstract: Background:There is mounting evidence that microRNAs play an important role in nasopharyngeal carcinoma, which is widely prevalent in South China and is the most prevalent metastatic cancer among head and neck cancers. Recently, it has been shown that miR-494 is involved in the progression and prognosis of nasopharyngeal carcinoma. However, little is known about the function and mechanism of miR-494-3p in nasopharyngeal carcinoma. In the present study, we aimed to investigate the effects of miR-494-3p on the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 47 publications
0
29
0
Order By: Relevance
“…MiRNAs play a significant role in different biological stages of NPC, such as cell viability, migration, invasion, epithelial‐mesenchymal transition, and apoptosis . For example, synthetic miR‐494‐3p mimics enhanced NPC cell proliferation, migration, and invasion via suppressing Sox7 expression . Although many studies have demonstrated the important influence of miR‐103/TIMP‐3 in human cancer pathogenesis, the interaction of miR‐103 and TIMP‐3 in NPC has not been examined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MiRNAs play a significant role in different biological stages of NPC, such as cell viability, migration, invasion, epithelial‐mesenchymal transition, and apoptosis . For example, synthetic miR‐494‐3p mimics enhanced NPC cell proliferation, migration, and invasion via suppressing Sox7 expression . Although many studies have demonstrated the important influence of miR‐103/TIMP‐3 in human cancer pathogenesis, the interaction of miR‐103 and TIMP‐3 in NPC has not been examined.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 For example, synthetic miR-494-3p mimics enhanced NPC cell proliferation, migration, and invasion via suppressing Sox7 expression. 27 Although many studies have demonstrated the important influence of miR-103/TIMP-3 in human cancer pathogenesis, 22 the interaction of miR-103 and TIMP-3 in NPC has not been examined. The higher miR-103 expression was observed in human NPC tissues and cells, and patients with low miR-103 expression had a clearly longer 5-year survival time, which was largely consistent with previous findings of the miR-103 effect.…”
Section: Discussionmentioning
confidence: 99%
“…It is highly malignant and is accompanied by local invasion and metastasis at an early stage. 1 A unique feature of NPC is its strikingly unusual ethnic and geographic distribution, as the incidence is significantly different in the USA in the white (0.8/ 100,000 persons per year) and Asian communities (7.6-10.7/100.000 persons per year). [2][3][4][5][6] It has been reported that the survival rates of early stage NPC patients reached 75-90%; however, they are less than 50% at the stage of metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the progress achieved in many therapeutic strategies, the underlying mechanism of NPC still remains largely unknown and the prognosis of cancer patients is also relatively poor [6,7].…”
mentioning
confidence: 99%